2006
DOI: 10.1103/physrevlett.97.165003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Static Dynamic Ergodic Divertor on Edge Turbulence Properties in TEXTOR

Abstract: Systematic measurements on the edge turbulence and turbulent transport have been made by Langmuir probe arrays on TEXTOR under various static Dynamic Ergodic Divertor (DED) configurations. Common features are observed. With the DED, in the ergodic zone the local turbulent flux reverses sign from radially outwards to inwards. The turbulence properties are profoundly modified by energy redistribution in frequency spectra and suppression of large scale eddies. The fluctuation poloidal phase velocity changes direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
58
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 22 publications
14
58
4
Order By: Relevance
“…In particular, a region of large positive E r , along the LCFS, can be noticed. This is a confirmation of the well-known presence of a positive E r in the stochastic edge of a tokamak [22,23,38,63,64,65,66,67,68]. But, if we focus on this region, we can note also a modulation in the poloidal angle, strictly linked to the magnetic topology, too: E r has a minimum in between the XP and the OP, and an absolute maximum in correspondence of the XP.…”
Section: Maps Of Plasma Potential: Experiments and Simulationssupporting
confidence: 54%
“…In particular, a region of large positive E r , along the LCFS, can be noticed. This is a confirmation of the well-known presence of a positive E r in the stochastic edge of a tokamak [22,23,38,63,64,65,66,67,68]. But, if we focus on this region, we can note also a modulation in the poloidal angle, strictly linked to the magnetic topology, too: E r has a minimum in between the XP and the OP, and an absolute maximum in correspondence of the XP.…”
Section: Maps Of Plasma Potential: Experiments and Simulationssupporting
confidence: 54%
“…19 particle flux as a result of RMPs was performed in low confinement L-mode. 20,21 The only work on fluctuation changes as a result of RMPs in H-mode was performed on DIII-D. 19,22,23 Moyer et al 22 showed at high collisionality that although magnetic fluctuations increase, there is no change to the radial electric field. However for low collisionality, the radial electric field in the pedestal area becomes more positive and at the same time the far infrared (FIR) coherent scattering (a non-localized measurement) shows that there is an increase in turbulence in the plasma edge.…”
Section: Introductionmentioning
confidence: 99%
“…density, can be applied to a possible suppression of instabilities due to impeding ١ ʈ n = 0. Finally it should be mentioned that in experiments 4 the turbulent E ϫ B-flux is not only reduced, it actually changes sign at least at certain locations.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The interest in three-dimensional turbulence simulations including complex magnetic topologies like open field lines, islands, and ergodic structures have been stimulated further by recent observations at DIII-D, 1,2 JET, 3 and at TEXTOR-DED. 4,5 There it has been proved that resonant magnetic perturbation fields have a beneficial effect for the control of bursty particle and heat transport. Typically the radial transport of particles and heat in the tokamak scrapeoff layer ͑SOL͒ is not smooth and steady but rather exhibits an intermittent, bursty behavior which occurs due to the presence of the last closed flux surface ͑LCFS͒, i.e., a boundary where an abrupt change from closed to open magnetic field lines occurs.…”
Section: Introductionmentioning
confidence: 99%